ShellBank: traceability toolkit and global database of marine turtle DNA - Michael P. Jensen; Greta J. Frankham; Carla Alonso O’Friel; Erin L. LaCasella; Kelly I. Morgan; Maftuna Sola; Lucy M. I. Webster; Peter H. Dutton; Christine A. Madden (Frontiers in Marine Science, 2026)
Effective conservation and enforcement strategies for marine turtles depend on understanding population structure, connectivity, and the geographic origins of turtles impacted by threats such as bycatch, overexploitation, and illegal trade. However, mitochondrial DNA (mtDNA) data remain fragmented across studies, with inconsistent sequence lengths, haplotype nomenclature, and metadata standards limiting their application in conservation, management, and wildlife forensics. To address these challenges, we developed ShellBank, a global marine turtle genetic traceability toolkit and open-access mtDNA database that consolidates and standardizes more than 20,000 mtDNA control-region sequences from published literature and verified contributed datasets. The platform harmonizes sequence lengths, haplotype nomenclature, and associated metadata, and provides tools to search haplotypes, access population-level baselines, extract frequency tables for Mixed Stock Analysis (MSA), and explore connectivity among nesting, in-water, and trade datasets. We demonstrate its utility through two case studies. First, mtDNA from a tortoiseshell seizure in the United Kingdom was compared against the ShellBank baseline, identifying likely source rookeries in the Eastern Caribbean and highlighting priority sampling gaps. Second, reanalysis of a hawksbill turtle foraging aggregation on the Great Barrier Reef using an expanded reference baseline substantially altered previous stock assignment estimates, corroborated flipper-tag and satellite-tracking data, and confirmed multi-stock connectivity across the western Pacific. By centralizing and standardizing global marine turtle mtDNA data, ShellBank improves the resolution, accuracy, transparency, and application of genetic traceability for conservation, management, and enforcement, strengthening the ability of researchers, managers, decision-makers, and enforcement agencies to identify source regions, detect population-level impacts, understand ecological connectivity, and guide evidence-based conservation actions.

Expanding the boundaries: regional connectivity in green turtle (Chelonia mydas) populations across Micronesia - Michael P. Jensen; Erin L. LaCasella; Donald R. Kobayashi; Amy Frey; Tammy M. Summers; Jessy R. Hapdei; George H. Balazs; Shawn K. K. Murakawa; T. Todd Jones; Summer L. Martin; Alexander R. Gaos; Peter H. Dutton (Frontiers in Marine Science, 2025)
The importance of ocean currents in influencing the connectivity and dispersal of marine megafauna, including sea turtles, is becoming increasingly recognized. However, more comprehensive studies are needed on how these currents impact the genetic makeup and connectivity of green turtle Chelonia mydas (Linnaeus, 1758) populations in the Pacific Islands region. To address this gap, our study conducted genetic analyses of green turtles in foraging grounds from four Micronesian sites and predictive modelling of hatchling dispersal patterns based on ocean currents to explore connectivity between foraging grounds and rookeries across Micronesia. We analyzed mitochondrial DNA (mtDNA) haplotype frequencies from newly collected and published data. We used Bayesian mixed stock analysis (MSA) to estimate the relative proportion of turtles from different Management Units (MUs) within the foraging grounds. Our ocean current simulations predicted hatchling dispersal trajectories, revealing how passive drift may facilitate wide-ranging dispersal and connectivity among distant foraging and nesting sites. Across the four Micronesian foraging grounds, the MSA revealed varying contributions from different rookeries, with some turtles exhibiting rare, long-distance dispersal traits. Our study highlights the intricate relationship between oceanic currents and the spatial dynamics of green turtles across the Pacific. Our findings offer essential insights into the conservation and management of green turtles by highlighting the role of oceanic currents in shaping population connectivity. Future research should focus on expanding genetic analyses and refining ocean drift simulations to enhance our understanding of marine megafauna migration and inform regional conservation strategies effectively.

Whole mitochondrial DNA sequencing improves resolution of population structure for Pacific green turtles (Chelonia mydas) - Amy Frey; Erin L. LaCasella; Michael P. Jensen; Peter H. Dutton (Frontiers in Marine Science, 2025)
Mitochondrial DNA (mtDNA) analysis is a key tool for defining population structure in marine turtles, due to their strong natal homing behavior, which leads to genetic differentiation among rookeries. However, the widespread occurrence of common haplotypes across large geographic areas, has limited the ability to resolve fine-scale population structure, particularly in the western Pacific. Understanding these population dynamics is crucial for effective conservation and management, as distinct nesting populations may face different threats. This study evaluates the use of whole mitochondrial genome sequencing to improve genetic resolution of population structure and enhance the accuracy of mixed stock analysis (MSA). We analyzed 197 nesting green turtles from six Pacific rookeries, representing two common mtDNA haplotypes (CmP20.1 and CmP22.1). Using mitochondrial capture enrichment and MSA simulations, we detected significant genetic differentiation between the rookeries in Guam and the Commonwealth of the Northern Mariana Islands (CNMI), which were previously considered a single genetic stock based on traditional control region sequencing. Our findings demonstrate that whole mitochondrial genome sequencing enhances stock resolution, improves the accuracy of MSA, and strengthens the ability to determine connectivity between nesting and foraging populations throughout the region. Refining genetics baselines using whole mitogenome sequencing will support more precise conservation strategies, allowing for targeted protection of genetically distinct populations, improved assessments of bycatch impacts, and better-informed management of critical foraging and nesting habitats.

Origins of green turtle fishery bycatch in the central Pacific revealed by mixed genetic markers - John B. Horne; Suzanne E. Roden; Erin L. LaCasella; Amy Frey; Summer L. Martin; T. Todd Jones; Shawn Murakawa; Shandell Brunson; George H. Balazs; Peter H. Dutton (Frontiers in Marine Science, 2023)
Longline fishing vessels, such as those that target tuna or billfish, also unintentionally catch endangered marine turtle species on the high seas. The stock composition of this bycatch is often unknown but potentially complex, with individuals coming from many possible origins on an ocean-basin scale. To better understand the stock composition of green turtle ( Chelonia mydas ) bycatch we obtained 46 turtles, 27-91 cm in curved carapace length, caught by Hawaii- and American Samoa-based pelagic longline fishing vessels across large areas of the North- and South-central Pacific. We genotyped these at nine microsatellite loci and one mitochondrial DNA marker, and used a baseline of 1,043 nesting female green turtles from beaches across the Pacific for population assignment and mixed-stock analysis. By analyzing both marker types jointly we were able to increase power and genetically resolve ten baseline stocks of nesting females with mean self-assignment and simulated accuracies of 75-97%. Above the Equator, green turtle bycatch was composed mostly of individuals from Hawaiian and Eastern Pacific stocks, with a small number from the Western Pacific. Below the Equator, the most common stocks in the bycatch were from Australia and the Coral Sea, American Samoa and French Polynesia, and the Galápagos Islands. Overall, turtles originating from East, West, and Central Pacific breeding populations were major components of the bycatch, suggesting that the geographic ranges of these populations overlap across large tracts of ocean during the pelagic life history stages.

United States Gulf of Mexico Waters provide important nursery habitat for Mexico’s Green turtle nesting populations - Brian M. Shamblin; Kristen M. Hart; Margaret M. Lamont; Donna J. Shaver; Peter H. Dutton; Erin L. LaCasella; Campbell J. Nairn (Frontiers in Marine Science, 2023)
Resolving natal populations for juvenile green turtles is challenging given their potential for extensive dispersal during the oceanic stage and ontogenetic shifts among nursery habitats. Mitochondrial DNA markers have elucidated patterns of connectivity between green turtle nesting populations (rookeries) and juvenile foraging aggregations. However, missing rookery baseline data and haplotype sharing among populations have often impeded inferences, including estimating origins of Gulf of Mexico juveniles. Here, we assessed genetic structure among seven foraging aggregations spanning southern Texas (TX) to southwestern Florida (SWFL), including Port Fourchon, Louisiana (LA); a surface-pelagic aggregation (SP) offshore of Louisiana and Florida; Santa Rosa Island, Florida (SRI); St. Joseph Bay, Florida (SJB); and the Big Bend region, Florida (BB). We estimated source contributions to aggregations with novel genetic data (excluding SP and BB) using a Bayesian many-to-one mixed stock analysis (MSA) approach. Haplotype frequencies for western (TX, LA, SP, SRI) and eastern (SJB, BB, SWFL) aggregations were significantly differentiated. The largest shift in haplotype frequencies between proximal nursery sites occurred between SRI and SJB, separated by only 150 km, highlighting the lack of a geographic yardstick for predicting genetic structure. In contrast to previous MSA results, there was no signal of Florida juveniles at any foraging site. Mexican contributions dominated in all aggregations, with strong connectivity between western Bay of Campeche (Tamaulipas/Veracruz) rookeries and western foraging aggregations. MSA indicated more diverse Mexican origins for eastern aggregations, with larger inputs from the eastern Bay of Campeche (Campeche/Yucatán), Campeche Bank, and Quintana Roo rookeries. These results demonstrate the significance of the Gulf of Mexico coast and offshore waters of the United States as important nursery habitat for green turtles of Mexican origin and highlight the need for international coordination for management of these populations.

Mitochondrial DNA Profiling to Combat the Illegal Trade in Tortoiseshell Products - Erin L. LaCasella; Michael P. Jensen; Christine A. Madden Hof; Ian P. Bell; Amy Frey; Peter H. Dutton (Frontiers in Marine Science, 2021)
Hawksbill turtles ( Eretmochelys imbricata ) are exploited for their beautiful shell known as tortoiseshell or bekko, making them extremely vulnerable in the illegal global trade of tortoiseshell products. In this study, we developed an effective, standardized method using a commercially available kit to extract DNA and obtain informative mitochondrial DNA (mtDNA) control region sequences (~800 bp) from hawksbill turtle products in order to trace the sample back to a likely stock origin. We also sequenced additional skin samples from nesting beaches of Milman Island, Australia and Arnavon Island, Solomon Islands to add to the baseline data for hawksbill turtles in the Indo-Pacific. Our results indicate that nine of the 13 tortoiseshell products obtained from Papua New Guinea and Solomon Islands were from turtles with haplotypes found primarily at the Solomon Islands rookery and did not match those from nesting populations in Australia or SE Asia, with the exception of one haplotype also found in 3% of turtles at Milman Island. We also found that 23% of the market samples have haplotypes only documented in foraging populations, which illustrates the urgent need for more extensive sampling of rookeries to fill gaps in the reference baseline database. Nevertheless, our study results demonstrate an effective methodology for obtaining DNA of sufficient quantity and quality from hawksbill turtle products.

Hawaiian hawksbills: a distinct and isolated nesting colony in the Central North Pacific Ocean revealed by mitochondrial DNA - Alexander R. Gaos; Erin L. LaCasella; Lauren Kurpita; George Balazs; Stacy Hargrove; Cheryl King; Hannah Bernard; T. Todd Jones; Peter H. Dutton (Conservation Genetics, 2020)

Finding Crush: Environmental DNA Analysis as a Tool for Tracking the Green Sea Turtle Chelonia mydas in a Marine Estuary - Kirsten J. Harper; Kelly D. Goodwin; Lynsey R. Harper; Erin L. LaCasella; Amy Frey; Peter H. Dutton (Frontiers in Marine Science, 2020)

Using mixed stock analysis to assess source populations for at‐sea bycaught juvenile and adult loggerhead turtles ( Caretta caretta ) in the north‐west Atlantic - Kelly R. Stewart; Erin L. LaCasella; Michael P. Jensen; Sheryan P. Epperly; Heather L. Haas; Lesley W. Stokes; Peter H. Dutton (Fish and Fisheries, 2019)
Assessments of fisheries by‐catch on marine megafauna are important for developing effective management strategies. For sea turtles, impacts may be evident in nesting population trends, but generally only after a lag, as turtles are slow to mature. We examined 850 loggerhead turtle ( Caretta caretta ) by‐catch samples collected over 14 years throughout the western North Atlantic to identify source nesting populations. We identified proportions of turtles from 19 distinct management units ( MU s), using mitochondrial DNA and mixed stock analysis, considering population size. We found a significant split in the distribution of small versus large loggerheads to the north and south of Cape Hatteras, North Carolina (latitude 35°N). North of Cape Hatteras, large turtles came from south‐east Florida ( SEFL ; 44% ± 15%) and the northern United States (33% ± 16%) MU s, while south of Cape Hatteras, the major contributors were Central East Florida (52% ± 20%) and south‐east Florida ( SEFL ; 41% ± 20%). Small turtles in the north came from Central East Florida (64% ± 14%), and in the south, south‐east Florida had the highest representation (56% ± 25%). There was little contribution from Mediterranean and Cape Verde populations, indicating low risk from western North Atlantic by‐catch to MUs in the Mediterranean. Understanding where threats may impact source populations is important, particularly for larger size turtles, as these individuals have the highest reproductive value. These findings allow more informed threat assessments to be conducted for loggerhead turtles considering spatial and demographic structure.

Genetic analysis and satellite tracking reveal origin of the green turtles in San Diego Bay - Peter H. Dutton; Robin A. LeRoux; Erin L. LaCasella; Jeffrey A. Seminoff; Tomoharu Eguchi; Donna L. Dutton (Marine Biology, 2019)

Population stock structure of leatherback turtles (Dermochelys coriacea) in the Atlantic revealed using mtDNA and microsatellite markers - Peter H. Dutton; Suzanne E. Roden; Kelly R. Stewart; Erin LaCasella; Manjula Tiwari; Angela Formia; Joao Carlos Thomé; Suzanne R. Livingstone; Scott Eckert; Didiher Chacon-Chaverri; Philippe Rivalan; Phil Allman (Conservation Genetics, 2013)

Natal homing in juvenile loggerhead turtles ( Caretta caretta ) - BRIAN W. BOWEN; ANNA L. BASS; SHAIO‐MEI CHOW; MEREDITH BOSTROM; KAREN A. BJORNDAL; ALAN B. BOLTEN; TOSHINORI OKUYAMA; BENJAMIN M. BOLKER; SHERYAN EPPERLY; ERIN LACASELLA; DONNA SHAVER; MARK DODD; et al. (Molecular Ecology, 2004)
Juvenile loggerhead turtles ( Caretta caretta ) from West Atlantic nesting beaches occupy oceanic (pelagic) habitats in the eastern Atlantic and Mediterranean, whereas larger juvenile turtles occupy shallow (neritic) habitats along the continental coastline of North America. Hence the switch from oceanic to neritic stage can involve a trans‐oceanic migration. Several researchers have suggested that at the end of the oceanic phase, juveniles are homing to feeding habitats in the vicinity of their natal rookery. To test the hypothesis of juvenile homing behaviour, we surveyed 10 juvenile feeding zones across the eastern USA with mitochondrial DNA control region sequences ( N = 1437) and compared these samples to potential source (nesting) populations in the Atlantic Ocean and Mediterranean Sea ( N = 465). The results indicated a shallow, but significant, population structure of neritic juveniles (Φ ST = 0.0088, P = 0.016), and haplotype frequency differences were significantly correlated between coastal feeding populations and adjacent nesting populations (Mantel test R 2 = 0.52, P = 0.001). Mixed stock analyses (using a Bayesian algorithm) indicated that juveniles occurred at elevated frequency in the vicinity of their natal rookery. Hence, all lines of evidence supported the hypothesis of juvenile homing in loggerhead turtles. While not as precise as the homing of breeding adults, this behaviour nonetheless places juvenile turtles in the vicinity of their natal nesting colonies. Some of the coastal hazards that affect declining nesting populations may also affect the next generation of turtles feeding in nearby habitats.